Epidemiological study of acquired syphilis in the South of Brazil - Nunes, Maria Beatriz da Cruz (2024)
The aim of this article is to carry out an epidemiological analysis of cases of acquired syphilis in southern Brazil between 2019 and 2023. This scientific work is a descriptive and quantitative ecological study, in which the Information and Notifiable Diseases System (SINAN) was used as a data source and the parameters used to collect information were: age group, race, sex and year of notification. Based on the data collected, it was found that the state of Rio Grande do Sul had the highest number of cases of acquired syphilis in southern Brazil. In addition, the male population aged between 20 and 39 proved to be the most susceptible to acquired syphilis. Based on the information in this article, it is clear that acquired syphilis is a public health problem in the South of Brazil. Measures are needed to better understand the disease, as well as public and private actions for early diagnosis and treatment of the disease, so that it will be possible to reduce the rates of acquired syphilis in the South of Brazil.